Religion and Tourism: Promoting Inclusive Islam in Lombok Island, Indonesia - Kadri, Kadri (Studia Islamika, 2022)
This article explores the empowerment and promotion of Inclusive Islam on the tourist island of Gili Trawangan, Lombok, Indonesia. The findings show that the Muslim community on this Island promotes inclusive values of Islam through the intensification of Islamic education for children, consistency of preaching, and the implementation of local norms based on Islamic values. Promoting inclusive Islam conducted indirectly through the implementation of tolerant Islamic teachings – without undermining or being undermined by the presence of tourist activities in the region, could make Islamic cultural events for tourism purposes and involve the mosque in the tourism business. This article argues that tolerance as one of the characteristics of inclusive Islam is not enough to be taught through formal and non-formal education, but needs to be maintained through social and economic activities. Therefore, this study recommends the important endeavours to preserve inclusive traditions of Islam in tourist destinations for religious and economic purposes.